Arranged Marriage: Adjusting Kafa’ah Can Reduce Trafficking of Women - Hafidzi, Anwar; Rusdiyah, Rusdiyah; Nurdin, Nurdin (Institut Agama Islam Negeri Curup, 2020)
This study aims to find the concept of match making or coercion in marriage against women. Women are more sensitive to match making issues and express disagreement with practices that violate women’s rights and endanger their future. However, previous researchers also considered match making coercion, sowe tried to research what if it was adapted to the concept of kafa'ah according to Shariah. The method used in this researchis a literature review by looking at the book an-nikah by Shaykh Muhammad Arsyad Al-Banjari, written in the 17th century AD. Through a hermeneuticalapproach, the researcher explores the marriage problems that her parents thought to becornering women in marriage problems. We try to uncover marriage problems that are sometimes considered to push women into marriage problems by their parents. This research proves that the concept of kafa'ah in al-Banjari theory can eliminate the perception of match making with a coercive system, because in the kafa'ah what is prioritized is a person's faith relationship which is ultimatelyable to maintain the honor of his wife and family. Not only in terms of material, but more inclined to approach immaterial needs. The Immaterial approach is evidenced by the harmonious relationship between the two families of the bride and groom.